Practical Basis for The Application of Didactic Game Technologies in Teaching Pedagogical Science - Hayitmuradova Shoira (Peerian Journals Publishing, 2022)
It is known that classes in which the cognitive activity of Students-Students is combined with gaming activity are called didactic game lessons. Didactic game technology consists of going to get the student-students ' knowledge acquisition along with the functioning of the game. Didactic games are important that they are conducted in the form of mutual assistance, cooperation. To do this, the teacher uses the didactic game for the intended purpose, the ways of its implementation, the content of the game and the activities of its participants. Didactic game lessons perform the task of teaching and upbringing, directing students 'activities, vocational guidance, developing students' communication and speech culture, deepening their knowledge and developing personality. In this article, opinions and reflections are made on the importance of didactic games in teaching pedagogical science and their use during training.
Keywords: technology; pedagogy; didactics; development